How the local built environment affects physical activity behaviour in older adults in the UK: a cross-sectional analysis linked to two national cohorts. (13th November 2015) - Hawkesworth, Sophie; Silverwood, Richard; Pliakas, Triantafyllos; Nanchahal, Kiran; Jefferis, Barbara; Sartini, Claudio; Amuzu, Antoinette; Armstrong, Ben; Casas, Juan-Pablo; Morris, Richard; Whincup, Peter; Lock, Karen
Abstract: Background: Policy makers are increasingly interested in how changes in local neighbourhood environments can affect health behaviours, especially physical activity, but individual studies rarely consider multiple environmental dimensions. Although older people can be particularly at risk of physical challenges in their local environment, few studies have focused on this age group. Methods: We developed a local environment audit instrument to capture multiple dimensions of the built environment that could affect the physical activity of older people; we linked the environmental data to physical activity behaviour collected in two nationally representative cohorts: the British Regional Heart Study and British Women's Heart and Health Study. Comprehensive foot-based audits were conducted by trained field staff in 20 towns across England and Scotland covering 590 lower super output areas and data zones; interobserver reliability of the instrument was high. The primary outcome was time spent in moderate-to-vigorous physical activity measured in participants for 1 week during 2010–12 with GT3X accelerometers (Actigraph, Pensacola, FL, USA). Using multilevel regression analysis, we assessed the association between aspects of the built environment and physical activity adjusted for individual-level confounders and area-level population density. Findings: 686 men and 638 women aged 69–92 years participated in the accelerometer study and were included in the analysis. Geometric mean time in moderate-to-vigorous physical activity was 26·3 min/day (geometric SD 2·7) in men and 23·8 min/day (SD 2·5) in women. There was no evidence of associations between any of the domains studied (quality of the built environment defined by latent class analysis; number of bus stops; area aesthetics; density of shops and services; amount of green space) and moderate-to-vigorous physical activity. Relative to areas with the worst quality walking environment, people living in areas with the best walking environments spent 2% more time in moderate-to-vigorous physical activity (95% CI −11 to 17, p=0·78 for overall trend). Interpretation: Although small effect sizes cannot be discounted, this study suggests that older individuals might be less affected by their local neighbourhood environment than is often presumed in the scientific literature, reflecting both the heterogeneous functionality of this age group and the varying nature of their activity spaces. Funding: This study was funded by a grant from the Medical Research Council (MR/J007145/1). The collection and extraction of data on physical activity in these cohorts was supported by grants from the British Heart Foundation (PG/09/024 and PG/13/66/304422) and National Institute for Health Research (PDF 2010-03-23).